Dimethylglycine Sodium Salt Alleviates Intrauterine Growth Restriction-Induced Low Growth Performance, Redox Status Imbalance, and Hepatic Mitochondrial Dysfunction in Suckling Piglets - Bai, Kaiwen; Jiang, Luyi; Wang, Tian (Frontiers in Veterinary Science, 2022)
This study aimed to investigate the mechanism of redox status imbalance and hepatic mitochondrial dysfunction induced by intrauterine growth restriction (IUGR) and relieve this condition through dimethylglycine sodium salt (DMG-Na) supplementation during the suckling period. Thirty normal birth weight (NBW) and 30 IUGR newborns were selected from 20 sows. Briefly, 1 NBW and 1 IUGR newborn were obtained from each litter of 10 sows, and 10 NBW and 10 IUGR newborns were obtained. Additionally, 2 NBW and 2 IUGR newborns were obtained from each litter of another 10 sows, and 20 NBW newborns were allocated to the N [basic milk diets (BMDs)] and ND (BMDs+0.1% DMG-Na) groups. Furthermore, 20 IUGR newborns were assigned to the I (BMDs) and ID (BMDs+0.1% DMG-Na) groups. The results revealed that the growth performance, serum and hepatic redox status, and hepatic gene and protein expression levels were lower (P < 0.05) in the I group compared to the N group. Additionally, supplementation with DMG-Na (ND and ID groups) improved (P < 0.05) these parameters compared to the non-supplemented groups (N and I groups). In conclusion, the activity of Nrf2/SIRT1/PGC1α was inhibited in IUGR newborns, and this led to their hepatic dysfunctions. Supplementation with DMG-Na activated Nrf2/SIRT1/PGC1α in IUGR newborns, thereby improving their performance.